Maternal eating behavior patterns and weight status of children - Aline Rabelo dos Santos; Marco Fábio Rabelo dos Santos (Revista Brasileira de Obesidade, Nutrição e Emagrecimento)
Objective: To evaluate the effects of maternal dietary patterns of cognitive restriction, emotional eating, and lack of food control on the nutritional status of children at 9 years of age. Materials and Methods: This is a cross-sectional study, which is part of a larger cohort study, covering 144 pairs of mothers and their children. For this study, sociodemographic, economic and anthropometric characteristics of the pair and the mother's dietary patterns will be evaluated. Results: The predictor variables: maternal nutritional status, nutritional status at birth and children who were born large for gestational age were significantly (p<0.05) associated with the nutritional status of children at nine years of age. In addition, cognitive restriction eating behavior was significantly higher among children who were overweight when compared to children ≤P85th percentile. Conclusions: The mother’s eating behaviors negatively influence the child’s weight status and are a potential risk factor for excess body weight in children.